2024
DOI: 10.18063/ijb.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma growth on trabecular bone mimicking structures manufactured via laser direct write

Abstract: This paper describes the direct laser write of a photocurable acrylate-based PolyHIPE (High Internal Phase Emulsion) to produce scaffolds with both macro-and microporosity, and the use of these scaffolds in osteosarcoma-based 3D cell culture. The macroporosity was introduced via the application of stereolithography to produce a classical "woodpile" structure with struts having an approximate diameter of 200 μm and pores were typically around 500 μm in diameter. The PolyHIPE retained its microporosity after ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Exactly on the same date, Sušec et al (2013) reported the development of stable photocurable thiolene HIPEs that can be used to produce PolyHIPEs using stereolithography. Fabrication of EHA:IBOA PolyHIPEs via stereolithography in wood-pile structure has been reported many times for various TE applications (Figure 10Bb; Malayeri et al, 2016;Owen et al, 2016;Wang et al, 2016). However, manufacturing of EHA:IBOA PolyHIPEs using stereolithography cause the formation of surface skin that is characterised with the closed pore at the surface.…”
Section: Stereolithographymentioning
confidence: 99%
See 1 more Smart Citation
“…Exactly on the same date, Sušec et al (2013) reported the development of stable photocurable thiolene HIPEs that can be used to produce PolyHIPEs using stereolithography. Fabrication of EHA:IBOA PolyHIPEs via stereolithography in wood-pile structure has been reported many times for various TE applications (Figure 10Bb; Malayeri et al, 2016;Owen et al, 2016;Wang et al, 2016). However, manufacturing of EHA:IBOA PolyHIPEs using stereolithography cause the formation of surface skin that is characterised with the closed pore at the surface.…”
Section: Stereolithographymentioning
confidence: 99%
“…Nalawade et al verified this finding on hydrogel-based HIPEs ( Nalawade et al, 2016 ). Trimethylolpropane triacrylate (TMPTA) is also widely used crosslinker for EHA and isobornyl acrylate (IBOA) PolyHIPEs ( Malayeri et al, 2016 ; Owen et al, 2016 ).…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
“…A. Malayeri et al developed a hierarchically porous polymer scaffold, known as a polyHIPE due to its synthesis using high internal phase emulsions (HIPEs), using 2-ethylhexyl acrylates (EHA) and isobornyl acrylate (IBOA) [ 55 ]. PolyHIPEs are a class of material where porosity is created via a phase-separation process, caused by mixing two immiscible liquids in the presence of an emulsifier [ 56 ].…”
Section: Stereolithographymentioning
confidence: 99%
“…29,57 Therefore, in preparation for cell culture, the surface chemistry of the polyHIPE microspheres was modified by inductively coupled plasma polymerisation of acrylic acid. The plasma polymerisation was carried out in a custom-made apparatus consisting of a cylindrical borosilicate glass chamber with stainless steel endplates connected to the vacuum pump (RV8, Edwards).…”
Section: Imaging Of Polyhipe Samplesmentioning
confidence: 99%